2014
DOI: 10.1371/journal.pone.0103099
|View full text |Cite
|
Sign up to set email alerts
|

In Silico Modeling of Human α2C-Adrenoreceptor Interaction with Filamin-2

Abstract: Vascular smooth muscle α2C-adrenoceptors (α2C-ARs) mediate vasoconstriction of small blood vessels, especially arterioles. Studies of endogenous receptors in human arteriolar smooth muscle cells (referred to as microVSM) and transiently transfected receptors in heterologous HEK293 cells show that the α2C-ARs are perinuclear receptors that translocate to the cell surface under cellular stress and elicit a biological response. Recent studies in microVSM unraveled a crucial role of Rap1A-Rho-ROCK-F-actin pathways… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
14
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(14 citation statements)
references
References 57 publications
0
14
0
Order By: Relevance
“…This intimate association appears to be mediated by a direct interaction between α 2C -ARs and filamin-2, a cross-linker of actin filaments (Motawea et al, 2013). Indeed, further in silico protein-protein docking examinations confirmed that the interaction between α 2C -AR and F-actin occurs via the direct binding of α 2C -AR to filamin, the actin binding protein (Pawlowski et al, 2014). Interestingly, this interaction has evolved only in warm blooded animals (Pawlowski et al, 2014).…”
Section: Rp and The Actin Cytoskeletonmentioning
confidence: 92%
See 1 more Smart Citation
“…This intimate association appears to be mediated by a direct interaction between α 2C -ARs and filamin-2, a cross-linker of actin filaments (Motawea et al, 2013). Indeed, further in silico protein-protein docking examinations confirmed that the interaction between α 2C -AR and F-actin occurs via the direct binding of α 2C -AR to filamin, the actin binding protein (Pawlowski et al, 2014). Interestingly, this interaction has evolved only in warm blooded animals (Pawlowski et al, 2014).…”
Section: Rp and The Actin Cytoskeletonmentioning
confidence: 92%
“…Indeed, further in silico protein-protein docking examinations confirmed that the interaction between α 2C -AR and F-actin occurs via the direct binding of α 2C -AR to filamin, the actin binding protein (Pawlowski et al, 2014). Interestingly, this interaction has evolved only in warm blooded animals (Pawlowski et al, 2014). Therefore, elucidation of similar protein-protein interactions can help establish more efficient therapies for exaggerated vasoconstriction.…”
Section: Rp and The Actin Cytoskeletonmentioning
confidence: 92%
“…Likewise, the structural model of either SmpB or ArfA was generated by submitting the amino acid sequence to the I-TASSER in comparison with SmpB (PDB code: 1k8h) or ArfA (PDB code: 2tmaA), accordingly. The output of I-TASSER was analyzed using Pymol version 1.4.1 (Pawlowski et al, 2014 ). HADDOCK (High Ambiguity Driven protein-protein DOCKing) was executed to dock SmpB and SN, ArfA and PA-2 separately (de Vries et al, 2010 ; van Zundert et al, 2016 ).…”
Section: Methodsmentioning
confidence: 99%
“…Further, structures were refined in explicit solvent and clustered according to HADDOCK score. Upon cluster-structural analysis, 10 lowest energy models were selected, and among these, the best one was characterized on the basis of lowest HADDOCK score, electrostatic energy and Z-score [ 38 , 39 ].…”
Section: Methodsmentioning
confidence: 99%